The mediating role of self-efficacy in the relationship between pedagogical competence and teacher performance in inclusive elementary schools - Marina Indriasari; Rubini B; Suhardi E (Indonesian Institute for Counseling, Education and Therapy (IICET), 2026)
Teacher performance in inclusive learning remains a critical issue, particularly in relation to pedagogical competence and teachers’ psychological readiness. This study examined the relationship between pedagogical competence and teacher performance in inclusive learning, with self-efficacy as a mediating variable. A quantitative cross-sectional survey was conducted involving 161 public elementary school teachers selected through proportional random sampling. Data were collected using validated questionnaires measuring teacher performance and self-efficacy, as well as a pedagogical competence test. The data were analyzed using path analysis, and the SITOREM method was used to determine priority areas for improvement. The findings showed that pedagogical competence positively influences teacher performance both directly and indirectly through self-efficacy. Self-efficacy was found to partially mediate the relationship between pedagogical competence and teacher performance in inclusive learning. These results indicate that improving teacher performance requires strengthening pedagogical competence while simultaneously enhancing teachers’ confidence in managing inclusive classrooms.